The Development of Collaborative Learning Talking Chips Based On Brain-Based Learning (BBL) for The Junior High School Science in The Agroecosystem Area - Ena Milada Tri Handayani; Jekti Prihatin; Kamalia Fikri (Pancaran Pendidikan, 2018)
Agroecosystem area has abundant natural resources, but these natural resources cannot be utilized as learning resources needed in the learning process of students becoming passive, comfortable and power-efficient in remembering students. Learning involving students is done by learning Brain-Based Learning (BBL) collaborated with Talking Chips type collaborative learning model. The purpose of this study is to obtain a development process, obtain a valid model, and obtain a Talking Chips learning a model based on Brain-Based Learning (BBL) that is practical for SMP learning in the Agroecosystem area. This research was conducted in SMP Negeri 9 Jember with research subjects of class VII B in the academic year 2018/2019. The type of this research was (research and development), using 4-D model Thiagarajan, but only used 3 stages define, design, and develop. The technique of collecting data is by collecting product validation data, test methods, interviews with teachers, questionnaire teachers and students and observations. The data analysis technique consisted of product validation analysis, analytic analysis with N-gain and learning retention, and practicality analysis. The product validation results, which are 89.33%, are categorized as very valid. The effectiveness of learning outcomes is 0.78 with a high category while the retention results obtained based on the learning retention analysis are 89 with a high category. The results of practicality obtained from the teacher questionnaire response were 98%, the category was very good and the questionnaire student responses were 96% with a very good category.